A comparative study of pharmacokinetics and bioequivalence of Cardiopril tablets 20 mg (JSC «Himfarm», Kazakhstan) and Monopril® tablets of 20 mg («Bristol-Myers Squibb SRL», Italy) - A. K. Sariev; D. A. Abaimov; M. V. Tankevich; S. A. Altinbekov; G. A. Dzholdygulov; V. N. Seryakov; Y. . Budach; O. . Kurilov (Фармакокинетика и Фармакодинамика)
In a single-dose, two-treatment, two-period, two-sequence crossover study with a 1-week washout period was carry out the bioequivalence study of two tablet coated formulation of fosinopril that given to 18 volunteers in equal doses (20 mg). Drug blood plasma concentrations were determined by validated LC-MS method for 48 hours. There were calculated the followed parameters: AUC 0-t ,Cmax, tmax , Cmax /AUC. 90% confidence interval for log-transformed AUC 0-tvalues was 0,9393 - 1,1473 and one for log-transformed Cmax was 0,8861 - 1,066, respectively. It was made the conclusion about bioequivalence of compared fosinopril formulations.